Jazz Music : History and Elements - Wichitwongwan, Supawit (Journal of Music and Performing Arts Khon Kaen University, 2023)
Academic articles on “Study of Jazz Band Mixing Techniques” is a academic issue to study the technique of combining jazz bands. focusing on the importance jazz band history The band’s approach and techniques for combining jazz from studying the history of jazz bands Jazz or jazz bands were formed by Negro slaves. New Orleans, Ohio, on the banks of the Mississippi River, USA after they were used as slaves. Blacks have to work hard and are heavily oppressed by whites. When they have free time from work, they come together to sing and dance. easy to use musical instruments to get rid of tiredness from work to relax Thus was born into jazz music. Later, it became popular all over the world and came into jazz in many ways, including Blue Jazz, New Orlean and Dixieland Style, Pop Style, Modern Style, etc.